The Influence of Service Quality on Customer Loyalty at PT Hagihara Westjava Industries - Pratiwi, Vira Mita Ajie; Kristanto, Yudi; Lesmana, Yanto (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The aim to be achieved by conducting this research is to find out how much influence service quality has on customer satisfaction. Based on the research results, it can be seen that the service quality at PT Hagihara Westjava Industries is quite good. This is indicated by the average value of the total score of 70.35, which is quite good.  The customers at PT Hagihara Westjava Industries are good. This is indicated by the average value of the total score of 79.59, which is good. There is an influence between Service Quality and Customer Satisfaction at PT Hagihara Westjava Industries because the calculated t value (9.327) is greater than the t table value (2.000) so that H1 is accepted and the calculated t value is located in the H0 rejection area. It was found that Service Quality has a strong positive influence (r value of 0.686) and has an influence contribution of 47% on Customer Satisfaction of PT Hagihara Westjava Industries. Meanwhile, the remaining 53% is influenced by other factors. The author also obtained a regression equation that can be used to predict the Customer Satisfaction variable through the Service Quality variable, namely Y' = 29.656 + 0.710.